Gestión del proceso de crédito y cobranzas y su incidencia en la rentabilidad de la cooperativa de ahorro y crédito sumak kawsay del cantón La Maná, año 2023. - Morán Ruiz, Landy Leonor (2024)
The development of this research work was carried out at the Coop. Sumak Kawsay Savings and Credit located in the La Maná canton. With the purpose of applying an evaluation to the management of the credit and collections process and its impact on profitability during the year 2023, who provides financial intermediation services through different types of credits according to the client's needs. Therefore, it is essential to evaluate compliance with regulations, which allowed determining the efficiency and effectiveness of its operations, applying management and profitability indicators, to establish the effectiveness of the portfolio recovery process that helped determine how the problem affected the company. Profitability of the cooperative. To develop the research, a field study was used with a descriptive, exploratory analysis that required the application of inductive and deductive methods that allowed us to know and point out the problems to be investigated. To collect the information, the survey technique was used using instruments such as questionnaires and interviews, in order to obtain the information required for the research. Resulting in the high rate of delinquency directly influencing the decreased profitability of the cooperative, due to the weaknesses in the management of the credit and collection processes. It should be noted that the research is viable since there was interest and predisposition on the part of the cooperative to improve the weaknesses that arose in the management of its processes.